Analysis of Language Style Uttered by the Characters in Premature Movie - Putra, I Made Pande Yoga; Santika, I Dewa Ayu Devi Maharani; Skolastika, I Made Perdana (Institut Pariwisata dan Bisnis Internasional, 2024)
Spoken language will always involve language style. This depends on the situation in which the conversation is taking place, and also the participants. This study was conducted to see the language style of the conversations in Premature movie. The data were analyzed by using qualitative method. The data analyzed based on the theory of language style proposed by Joos (1967), and it combined with the theory of function of language proposed by Holmes (1992). The data were taken from the conversation that uttered by the characters in Premature movie. Based on the analysis there are 19 data that found in the data source, there are four types of language style and six types of language function were found. The four language styles are four types of language style which are, formal style, consultative style, casual style, and intimate style. Casual style is the most dominant type in this movie. The six function of language that found by the researcher which are expressive function, directive function, referential function, metalinguistic function, poetic function, and phatic function. The most function of language occurred in the data analysis is directive function.